Peran Guru Bimbingan Konseling dalam Mengembangkan Kemandirian Belajar Siswa Madrasah Aliyah Swasta Muallimin Univa Medan: The Role of Guidance and Counseling Teachers in Developing Learning Independence of Students at Muallimin Univa Medan Private Islamic Senior High School - Ayu Ari Lestari; Abdul Aziz Rusman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Based on the results of initial observations, some students have problems with student learning independence, such as low self-confidence, lack of discipline, lack of responsibility, dependence on others, and lack of initiative. The purpose of this study is: (1) to describe guidance and counseling services in developing student learning independence. (2) To describe factors that can influence learning independence. (3) To describe learning independence. This type of research is qualitative research through a descriptive approach. Data sources are primary data and secondary data. The method used is qualitative with a narrative research design to find facts with the correct interpretation; research can involve various combinations of interview data and documentation to make an analysis. Data collection techniques are interviews and documentation of data validity. The results that researchers can conclude are that the role of guidance and counseling teachers in developing student learning independence is very appropriate because learning independence is the principal capital students must have. Guidance and counseling teachers are considered the correct figures to solve problems of student learning independence. Based on the results of research related to student learning independence, there are still students who do not fully have a responsible attitude in learning, are not active and creative in learning; it can be seen that there are still students who lack self-confidence, are unable to solve learning problems and lack interest in seeking new sources of knowledge.